Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Test - Page 578: 23



Work Step by Step

Simplify. $ (11x+6)^{\frac{1}{3}}=-3$ Take cubic on both sides. we have, $ (11x+6)=(-3)^3$ or, $11x+6=-27$ After simplifications,we have Thus, $11x=-27-6$ Hence, we can conclude that $x=-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.